On the Cross-Country Relationship between Poverty, Income Distribution, and Development - Karshenas, Massoud; Pyatt, Graham (Journal of Income Distribution®, 2014)
The familiar cross-country relationship between the incidence of poverty and the level of development is derived via a three-stage process, which avoids restrictive parametric assumptions regarding the shape of income distribution. It starts with the relationship within a given household survey data set between the incidence of poverty and the mean value of the ratio m/z, where m is a measure of individual well-being and z is the critical value of m relative to which the poor are identified. It is then shown that there is a one-to-one relationship between this relationship and the Lorenz curve. In the second stage of our analysis we establish inter alia a sufficient condition for the incidence of poverty to be less in whichever of any two countries the average value of m/z is smaller. These conditions are tested empirically. Conditions under which this average value will be proportional to the Gross Domestic Product per capita (GDP) are identified in the third stage. Both the second and third stages of our procedure provide opportunities for improving on the ’explanation’ of poverty offered by the GDP per capita. In particular, the Sen Index apparently provides a much better way of accounting for differences in the incidence of poverty across countries. The importance of economic growth for reducing poverty should be qualified accordingly.